MR Neurography of the Lumbosacral Plexus for Lower Extremity Radiculopathy: Frequency of Findings, Characteristics of Abnormal Intraneural Signal, and Correlation with Electromyography - Chazen, J.L.; Cornman-Homonoff, J.; Zhao, Y.; Sein, M.; Feuer, N. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: MR neurography enables high resolution imaging of peripheral nerves. Our aim was to evaluate the utility of MR neurography in lumbosacral radiculopathy and correlate abnormal intraneural signal with history, physical examination, and abnormal electrodiagnostic study findings.MATERIALS AND METHODS: Retrospective review of lumbosacral MR neurography examinations performed from December 2014 through January 2017 on a 3T scanner was undertaken. MR neurography examinations were independently reviewed in a blinded fashion by 2 radiologists, and the intraneural signal was graded on a 0–2 scale relative to adjacent vasculature. Abnormal nerve signal was correlated with subjective and objective findings from clinical notes in the electronic medical record and compared with results of electrodiagnostic studies (nerve conduction study/electromyography).RESULTS: Three hundred three lumbosacral MR neurography examinations were performed during the study period, 64 of which met the inclusion criteria, including symptoms of radiculopathy on electromyography performed within 3 months of MR neurography. Twenty-nine (45%) MR neurography examinations had abnormal intraneural signal. There was no statistically significant correlation between subjective clinical findings and intraneural signal abnormality on MR neurography. There was a statistically significant correlation between abnormal intraneural T2 signal and findings of active radiculopathy on electromyography (P < .001).CONCLUSIONS: Lumbosacral MR neurography appears to demonstrate abnormal intraneural signal in a substantial portion of patients with clinical symptoms of lower extremity radiculopathy and correlates with findings of active radiculopathy on electromyography. This finding further bolsters the growing body of evidence on the utility of MR neurography and suggests that abnormal intraneural signal may provide a useful adjunct to electrodiagnostic testing. Further research is required to evaluate the prognostic value of MR neurography, which may help guide therapeutic decision-making.EMGelectromyographyMRNMR neurographyMUAPmotor unit action potentialNCSnerve conduction studySPAIRspectral adiabatic inversion recovery